Impact of persistent subclinical hypothyroidism on clinical outcomes in non‐ST‐segment elevation acute coronary syndrome undergoing percutaneous coronary intervention. (12th October 2021) - Han, Chuyi; Xu, Kaihang; Wang, Le; Zhang, Yingyi; Zhang, Rui; Wei, Ao; Dong, Lijie; Hu, Yuecheng; Xu, Jinghan; Li, Wenyu; Li, Tingting; Liu, Chunwei; et al.
Abstract: Background: Data on the association of subclinical hypothyroidism (SCH) with the severity of coronary artery disease and major adverse cardiovascular and cerebral events (MACCE) in patients with non‐ST‐segment elevation acute coronary syndrome (NSTE‐ACS) after percutaneous coronary intervention (PCI) are limited and conflicting. Objective: We established the baseline rate of SCH and followed the trajectory of thyroid‐stimulating hormone (TSH) values during and after hospitalisation for PCI for up to six months and determined whether persistent SCH was associated with the severity of coronary artery disease and MACCE in patients with NSTE‐ACS after PCI. Design: Population‐based prospective cohort study. Patients: We included patients with NSTE‐ACS who underwent PCI with simple balloon angioplasty or stent implantation for coronary heart disease. Measurements: Thyroid function tests of patients before PCI and 1 day, 1 week, 1 and 6 months after PCI were performed. Cases showing transient SCH were excluded. Patients were divided into two groups based on the results of four TSH tests: 0.27–4.2 mIU/L ( n  = 1472, 89.7%) and >4.2 mIU/L ( n  = 170, 10.4%). The risk factors for the severity of coronary artery lesions were estimated using multinomial logistic regression analysis. Univariate and multivariate Cox regression analyses were used to study the relationship between TSH and MACCE. Results: Among 1642 patients, there were 1070 males (65.2%) and 572 females (34.8%), with an average age of 62.5 ± 9.6 years. SCH patients had a wider range of diseased vessels and a higher number of diseased vessels ( p  < .05). TSH level was an independent risk factor for moderate [odds ratio (OR) = 1.144, 95% confidence interval (95% CI): 1.057–1.237, p  = .001] and severe (OR = 1.131, 95% CI: 1.043–1.226, p  = .003) coronary artery lesions. After adjusting for covariates, the risk of MACCE [hazard ratio (HR): 4.067, p  < .001], nonfatal myocardial infarction (HR: 14.724, p  = .003), and unplanned PCI (HR: 5.028, p  < .001) were higher in the SCH group than in the euthyroidism group. There were no significant differences in the incidence of heart failure (HR: 6.012, p  = .175), nonfatal stroke (HR: 2.039, p  = .302), unplanned coronary artery bypass grafting (CABG) (HR: 1.541, p  = .57), or cardiac death (HR: 2.704, p  = .375) between the two groups. Conclusions: Preoperative TSH levels and changes in thyroid hormone levels several months post‐PCI in NSTE‐ACS patients are highly significant in practice. Persistent SCH is associated with severe coronary artery lesions and MACCE, and may be a predictor for evaluating the prognosis of PCI‐treated NSTE‐ACS patients.